PELATIHAN PUBLIC SPEAKING UNTUK SISWA SMA: PENDEKATAN KARAKTER KEPRIBADIAN UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI PUBLIK - Winarko, Hilarius Bambang (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Public speaking skills are essential in various aspects of life, including academic and professional environments. This article discusses the implementation of the public speaking workshop for students of SMA Santo Kristoforus II Jakarta, organized by Universitas Bunda Mulia (UBM) as part of community service activities. The workshop aims to enhance students’ understanding of the basic elements of public communication, recognize personality traits, and practice public speaking skills. The workshop methods include material presentations, case studies, and hands-on practice using the Personality Plus approach, which categorizes personalities into four types: Sanguine, Choleric, Melancholic, and Phlegmatic. The case study of Greta Thunberg, a young environmental activist with communication limitations, was used as an inspiration to overcome public speaking anxiety. The training results indicate an increase in students’ self-confidence and a better understanding of how to adapt communication styles based on personality characteristics. This training is expected to have a lasting positive impact on students, both in academic contexts and their future social interactions.